(untitled) (Costos y Gestión, 2021)
The automobile industry in Argentina is going through a critical moment due to the macroeconomic crisis that the country is facing, in order to survive this situation, the companies are looking for tools that provide critical information when making decisions of great impact for it. One of the tools they use is marginal analysis, since it allows us to identify the sensitivity of costs or other financial variables in certain decisions; thus achieving the maximum profit. For example, when faced with decisions to change production or decrease costs, we can identify which are the most critical variables when faced with different decisions and their impacts in the company. In addition, we can define scenarios and determine which of all would maximize the benefit or what actions to take in the face of different events that may occur. Today in Argentina this is very useful due to the volatile situation that exists, thus allowing to prepare in advance for these situations and to know what decisions to make. In conclusion, as we can see here, marginal analysis is a very important and effective tool when it comes to providing relevant information for decision-making, both for cost reduction and adaptation of the environment; helping to focus on the relevant variables or costs that will give us the greatest benefit.